Transcutaneous auricular vagus nerve stimulation may benefit from the addition of N-acetylcysteine to facilitate motor learning in infants of diabetic mothers failing oral feeds - Jenkins, Dorothea D.; Garner, Sandra S.; Brennan, Alyssa; Morris, Jessica; Bonham, Kate; Adams, Lauren; Hunt, Sally; Moss, Hunter; Badran, Bashar W.; George, Mark S.; Wiest, Donald B. (Frontiers in Human Neuroscience, 2024)
Objective This study aims to determine if pretreating with enteral N-acetylcysteine (NAC) improves CNS oxidative stress and facilitates improvement in oromotor skills during transcutaneous auricular nerve stimulation (taVNS) paired with oral feedings in infants of diabetic mothers (IDMs) who are failing oral feeds. Methods We treated 10 IDMs who were gastrostomy tube candidates in an open-label trial of NAC and taVNS paired with oral feeding. NAC (75 or 100 mg/kg/dose) was given by nasogastric (NG) administration every 6 h for 4 days, then combined with taVNS paired with 2 daily feeds for another 14 days. NAC pharmacokinetic (PK) parameters were determined from plasma concentrations at baseline and at steady state on day 4 of treatment in conjunction with magnetic resonance spectroscopic (MRS) quantification of CNS glutathione (GSH) as a marker of oxidative stress. We compared increases in oral feeding volumes before and during taVNS treatment and with a prior cohort of 12 IDMs who largely failed to achieve full oral feeds with taVNS alone. Results NAC 100 mg/kg/dose every 6 h NG resulted in plasma [NAC] that increased [GSH] in the basal ganglia with a mean of 0.13 ± 0.08 mM (p = 0.01, compared to baseline). Mean daily feeding volumes increased over 14 days of NAC + taVNS compared to the 14 days before treatment and compared to the prior cohort of 12 IDMs treated with taVNS alone. Seven IDMs reached full oral feeds sufficient for discharge, while three continued to have inadequate intake. Conclusion In IDM failing oral feeds, NAC 100 mg/kg/dose every 6 h NG for 4 days before and during taVNS paired with oral feeding increased CNS GSH, potentially mitigating oxidative stress, and was associated with improving functional feeding outcomes compared to taVNS alone in a prior cohort. This represents a novel approach to neuromodulation and supports the concept that mitigation of ongoing oxidative stress may increase response to taVNS paired with a motor task.